Determination of cations and metals in samples of beer and raw materials for beer production by ion chromatography (IC) and atomic absorption spectrophotometry (AAS) methods - Slobodan Prijić; Ljubiša Ignjatović (Zaštita Materijala)
In order to control the quality of beer and raw materials for beer production, methods as ion chromatography (IC) and atomic absorption spectrophotometry (AAS) were applied. Water was analyzed as a raw material for beer production (urban, technological and demineralized water). Measurements of pH values indicated the increased pH values in the sample of tehnological water, but it had no impact on wort hopping, since the tested samples of wort, young beer and final product had a pH value in the expected range. Analyzing the content of anions and cations in the examinated water samples, it is shown that the concentration of these examinated anions (Cl- , NO3-, SO42- and PO43-) and cations (NH4+, Na+, K+, Ca2+, Mg2+), as and microelements (Fe, Cu i Zn) are within the limits prescribed by the Regulations on hygienic safety of drinking water and the Regulations of quality and other requirements for beer. Investigating contents of anions in samples of wort and beer (young beer and final product) showed that the contents of SO42- and NO3- ions were within recommended limits and the concentration of Cl- ions was above 150 mg/dm3, which may have an impact on sensory characteristics of beer, while changes in the content of PO43- ions were insignificant. Since AAS method is a standard method for analyzing content of alkaline and alkaline earth metals, the results obtained by this method in beer samples are taken as a referent results and according to them an analyse was performed and results obtained by IC method were compared. Results of the determination of Na, Ca and Mg in examinated water samples have shown variations, but both methods have shown the increased content of Na in demineralized water. The contents of alkaline and alkaline earth metals in wort and beer (young beer and final product) have shown that the results obtained by these two methods were in agreement.